THE INFLUENCE OF MODAL STRUCTURE, THE SIZE OF THE COMPANY AND SALES GROWTH ON COMPANIES PROFITABILITY THAT LISTED ON SRI-KEHATI INDEX - Arif Herlambang; Putu Anom Mahadwarta; Niafatul Aini (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2016)
The purpose of this paper is investigate the impact of capital structure growth on firm profitability from companies that listed on SRI-KEHATI Indeks in 2011-2015. Independent variable that used to represent firm profitability is Return on Asset (ROA), while the independent variables that used to represent long term debt, short term debt, firm size, and sales growth. The data used in this study is secondary data derived from the financial statements of companies listed in the SRI-KEHATI index period 2011-2015. Data analysis technique in this research use regression analysis of panel data of Fixed Effect Model (FEM). From the test, it can be seen that the variable of long-term debt, short term debt, firm size and sales growth give significant influence to profitability of companies listed in SRI-KEHATI index in 2011-2015 period.